Comparison of modern fluid distribution, pressure and flow in sediments associated with anticlines growing in deepwater (Brunei) and continental environments (Iran) - Morley, C.; Warren, J.; Tingay, Mark; Boonyasaknanon, P.; Julapour, A. (Elsevier, 2014)
Differences in fluids origin, creation of overpressure and migration are compared for end member Neogene fold and thrust environments: the deepwater region offshore Brunei (shale detachment), and the onshore, arid Central Basin of Iran (salt detachment). Variations in overpressure mechanism arise from a) the availability of water trapped in pore-space during early burial (deepwater marine environment vs arid, continental environment), and b) the depth/temperature at which mechanical compaction becomes a secondary effect and chemical processes start to dominate overpressure development. Chemical reactions associated with smectite rich mud rocks in Iran occur shallow (~1900 m, smectite to illite transformation) causing load-transfer related (moderate) overpressures, whereas mechanical compaction and inflationary overpressures dominate smectite poor mud rocks offshore Brunei. The basal detachment in deepwater Brunei generally lies below temperatures of about 150°C, where chemical processes and metagenesis are inferred to drive overpressure development. Overall the deepwater Brunei system is very water rich, and multiple opportunities for overpressure generation and fluid leakage have occurred throughout the growth of the anticlines. The result is a wide variety of fluid migration pathways and structures from deep to shallow levels (particularly mud dykes, sills, laccoliths, volcanoes and pipes, fluid escape pipes, crestal normal faults, thrust faults) and widespread inflationary-type overpressure. In the Central Basin the near surface environment is water limited. Mechanical and chemical compaction led to moderate overpressure development above the Upper Red Formation evaporites. Only below thick Early Miocene evaporites have near lithostatic overpressures developed in carbonates and marls affected by a wide range of overpressure mechanisms. Fluid leakage episodes across the evaporites have either been very few or absent in most areas. Locations where leakage can episodically occur (e.g. detaching thrusts, deep normal faults, salt welds) are sparse. However, in both Iran and Brunei crestal normal faults play an important role in the transmission of fluids in the upper regions of folds.